Promoting Prediction Strategy in Comprehending PISA Reading Text for Students at Universitas Timor - Delti Yulita; Febronia Lasi; Emanuel M. Y Hano'e (Fakultas Keguruan dan Ilmu Pendidikan-Universitas Timor, 2025)
The ability to comprehend a higher level of text is important in this new era. In order to achieve the comprehension, students need more effective strategy in reading. Thus, this activity is promoting making prediction strategy in purpose to help students to engage with PISA reading text that require higher level of thinking. By making prediction, the students are trained to use their prior knowledge and connect it with the new information from the text. This activity was conducted in Universitas Timor and attended by 29 students in critical reading class. The results showed that prediction strategy effectively improve students’ comprehension and change their reading behaviour. The prediction test classified 70% of the students were in grade 4 and 3 at making prediction while the 30% were in grade 1 and 2. The excellent students were exposed that making prediction help them to actively interacting with the text and trained their mind to think and predict before, during and after reading. The students with low grade revealed their difficulties were in understanding the main idea and didn’t know how to use their prior knowledge. Therefore, it is necessary for the students to practice brainstorming to activate their prior knowledge.